AKIBAT HUKUM TERHADAP DEBITUR ATAS TERJADINYA FORCE MAJEURE (KEADAAN MEMAKSA) - Parama Adhi Wibawa, Putu; Artadi, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014)
Engagement is a legal relation on wealth between two or more people, on thebasis of a party reserves the right (creditor) and the other party is obliged to (debtor)for something accomplishment. In the engagement, if the debtor doesn’t voluntarilymeet their obligations in good faith, then the creditor may request the assistance of lawpush the debtor to fulfil its obligation. Force majeure regulated in Article 1244 of theCivil Code. This article is about the restitution payment, as well as issues related to theburden of proof, in the event of default, the debtor sentenced to pay the restitution if thedebtor couldn’t prove that a default was caused by unexpected circumstances or beyondthe ability of the debtor. Debtor has an obligation to do something, but it turns out thatthe debtor doesn’t fulfil its obligations, then the resulting losses on the debtor. Thepurpose of this paper is to understand the elements of force majeure and to determinethe legal consequences of the debtor upon the occurrence of a force majeure. By usingthe normative method, the conclusion discovered that there are two theories about forcemajeure, namely the theory of absolute and the theory of relative. According to thetheory of absolute, the debtor in the state of force majeure, if the fulfillment of theachievement is not possible to be fulfilled by anyone. While according to the theory ofrelative, force majeure occurs when debtor might have a chance to fulfill theachievement with a big sacrifice. A result of negligence causing the force majeure thenthe debtor unable to perform its obligation in accordance with what has been agreedand the debtor must replace the losses incurred.
Keywords: legal consequence, debtor, force majure